THE POWER OF INTEREST AND PROFITABILITY RATES IN FINANCIAL MARKET DEVELOPMENT - ugli, Firdavs Kazakov Farhod (Antis Publisher, 2024)
This comprehensive article explores the pivotal role of interest and profitability rates in shaping financial market development. Focusing on the interplay between these rates and market behavior, the essay examines their influence on investment decisions, economic stability, and overall market performance. Drawing on insights from financial theory, empirical research, and real-world examples, the article elucidates the complex dynamics underlying the relationship between interest rates, profitability, and financial market growth. With a nuanced analysis of various financial intermediaries, debt markets, and channels for fund transfer, the article provides valuable insights into the mechanisms driving financial market development